200 Defining Normal: Flow Cytometry Immunophenotyping of Benign Lymph Nodes Sampled by Fine Needle Aspiration or Surgical Biopsy. (11th January 2018) - Scott, Gregory; Gratzinger, Dita
Abstract: Large-scale normative data are lacking for benign lymph nodes assessed by flow cytometry immunophenotyping. Initial diagnostics are increasingly moving toward fine needle aspiration (FNA). We used a novel informatics approach to gather large-scale normative data for benign lymph node flow cytometry and compare the performance of flow cytometry immunophenotyping from samples obtained by excisional biopsy vs FNA. We hypothesized that a large normative immunophenotyping dataset will demonstrate comparability between excisional biopsies and FNA flow cytometry immunophenotyping results. Custom text-parsing software was created to extract clinical, diagnostic, and flow cytometry data from 382 consecutive excisional biopsies and 309 consecutive FNAs carrying a benign diagnosis and spanning the last 15 years. Antigens normalized to B- and T-cell content were compared between excisional biopsy and FNAs by t -test corrected for multiple comparisons by false discovery rate. As expected, raw numbers of events were lower in the FNA as compared to the excisional biopsies (86.0% vs 82%). Excisional biopsy vs FNA samples had a significantly lower proportion of events in the monocyte gate (6.5% vs 4.3%). FNAs were enriched for CD3+ T cell events (70.1% vs 59.4%) and with proportionately fewer CD19+ B cells events (23.8% vs 32.7%). Nevertheless, normalized B-cell subsets (eg, %CD19/CD10+, %CD19/CD5+) and T-cell subsets (eg, CD4:CD8 ratio) did not significantly differ between excisional biopsy and FNA specimens with minor exceptions. In conclusion, excisional biopsy and FNA samples differ in overall yield as well as T-cell content, likely due to peripheral blood contamination, but nevertheless produce comparable immunophenotyping results with respect to B- and T-cell subsets in benign lymph nodes. Informatics approaches enlarge normative datasets and in the current study led to the first large-scale quantitative comparison of normative data between different tissue-sampling methods.